The effect of eye-foot coordination, leg muscle strength and mental skills on the shooting skills of bangka football school athletes (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2022)
This study aims to determine the effect of eye-foot coordination, leg muscle strength, and mental skills on the shooting skills of Bangka Football School athletes. The research method used is an associative quantitative approach with non-test techniques, while the analysis technique uses a path analysis approach. This research was conducted at SSB Selindung 89, Bangka, aged 9-12 years, totaling 36 people. To measure shooting skills, use a ball shooting skill test which is placed at a point 8 m in front of the goal/target. Test your eye-foot coordination by kicking the ball against a wall or the Threebox Wall Soccer Test. Test leg muscle strength using a leg dynamometer with three trials. While the mental skills test uses a questionnaire. Conclusions from the results of the study 1) Eye-foot coordination has a direct effect on shooting skills by 34.1%. 2) Leg muscle strength has a direct effect on shooting skills by 45.3%. 3) Mental skills directly affect shooting skills by 35.4%. 4) Eye-foot coordination has a direct effect on mental skills by 23.5%. 5) Leg muscle strength has a direct effect on mental skills by 44.8%. 6) Eye-foot coordination has an indirect effect on shooting skills of athletes through mental skills of 50.7%. 7) Leg muscle strength has an indirect effect on athletes' shooting skills through mental skills of 43.8%. Keywords: Eye-Foot Coordination, Leg Muscles, Mental Skills, Shooting